2016
DOI: 10.5935/abc.20160177
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heart Rate Variability Before and During Tilt Test in Patients with Cardioinhibitory Vasovagal Syncope

Abstract: BackgroundCardioinhibitory vasovagal response is uncommon during the tilt test (TT). Heart rate variability (HRV) by use of spectral analysis can distinguish patients with that response.ObjectiveTo compare the HRV in patients with cardioinhibitory vasovagal syncope (case group - G1) with that in patients without syncope and with negative response to TT (control group - G2).Methods64 patients were evaluated (mean age, 36.2 years; 35 men) and submitted to TT at 70 degrees, under digital Holter monitoring. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
2
12
0
3
Order By: Relevance
“…Phase 2 (Passive Tilt): the LF power of SBPV showed continuous decrement during this phase, which was different from the plateau pattern of LF power of HRV. Conflicting results about the LF power activity during the passive phase of HUTT has been reported, showing plateau responses, 25 increased activity, 26 and decreased activity. 27 Therefore the pattern of LF power activity in SBPV may be a correct response because it is not under the influence of other factors like baroreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 90%
“…Phase 2 (Passive Tilt): the LF power of SBPV showed continuous decrement during this phase, which was different from the plateau pattern of LF power of HRV. Conflicting results about the LF power activity during the passive phase of HUTT has been reported, showing plateau responses, 25 increased activity, 26 and decreased activity. 27 Therefore the pattern of LF power activity in SBPV may be a correct response because it is not under the influence of other factors like baroreceptor sensitivity.…”
Section: Discussionmentioning
confidence: 90%
“…[ 19 , 20 ] Miranda et al reported that elevation in the LF/HF ratio and a decrease in HF were observed when the head was up during the TTT in patients with syncope. [ 21 ] Moreover, they reported that this phenomenon was more pronounced in these patients than in healthy subjects. The autonomic nerve balance in this case changed during the 10:00 to 12:00 period, which is a similar situation to what occurs during tilt-up in the TTT and might lead to syncope.…”
Section: Discussionmentioning
confidence: 95%
“…There have been attempts to use HRV analyses to predict the outcome of TTT and through this to improve the diagnosis of VVS, with variable degrees of success (Ciliberti et al, 2018;Klemenc and Štrumbelj, 2015;Miranda and Silva, 2016;Zheng et al, 2020).…”
Section: Heart Rate Variability In Vvsmentioning
confidence: 99%